Economic Valuation of Food Crop Agricultural Activities in Bleberan Village, Playen Sub-District, Gunungkidul District In 2022 - Muhammad Miftahurridlo; Sudrajat; Harini, Rika (AESE Journal, 2024)
Amid Indonesia’s agricultural landscape, Bleberan Village and Playen sub-district face a pressing challenge – the diminishing availability of agricultural land. Recognizing agriculture’s pivotal role in Indonesia, this research confronts the stark reality of land scarcity exacerbated by the adverse environmental impacts of modern farming practices. The study examines the causes of land degradation and discovers various variables while criticizing previous methods. A quantitative descriptive research method is used to explore the benefits of food crop farming and reveal their high economic value. The results underscore the multifaceted advantages of food crop cultivation, highlighting its vital role in the local economy. The significance of this research lies in its revelation of the critical importance of food crop farming in the face of diminishing agricultural land. The findings contribute valuable insights to the existing discourse on sustainable farm development and underscore the urgency of implementing specific strategies to counteract the challenges posed by land scarcity. As we navigate the complex intersection of economic, environmental, and agricultural concerns, this research serves as a beacon, illuminating the path toward a more resilient and sustainable future for Bleberan Village and the Playen sub-district.